Assessing Food Waste Compost as a Substrate Amendment for Tomato and Watermelon Seedlings - Allyson N. Hamilton; Matthew B. Bertucci; Kristen E. Gibson; Mary C. Savin; D.E. Kirkpatrick; R.C. Woody-Pumford (HortTechnology)
A greenhouse study investigated the influence of various food waste compost (FWC) and potting mix (PM) blends on germination, growth, and nutrient uptake of tomato (Solanum lycopersicum) and watermelon (Citrullus lanatus) seedlings. Source material for the FWC included food scraps from a commercial partner and wood chips from a local tree service company. The FWC was prepared in a controlled environment and combined with wood chips to create experimental substrates. After composting, substrate blends were prepared by mixing FWC with a peat-based PM to create five volume:volume (v:v) ratios of FWC:PM comprising 100:0 (FWC alone), 75:25, 50:50, 25:75, and 0:100 (PM alone). Tomato and watermelon growth characteristics were assessed during separate trials in the same greenhouse. For each trial, one seed was sown into each cell of a 72-cell tray filled with a corresponding substrate. Plant growth assessments included emergence rates, plant height, stem diameter, biomass, leaf area, and nutrient content. Tomato emergence was reduced to 67% and 77% in 75:25 (FWC:PM) and FWC alone, respectively; however, higher PM substrate blends had 88% to 92% tomato emergence. Watermelon emergence was 62% in FWC alone, whereas all other substrate blends had ≥81% watermelon emergence. The results indicated that substrate mixes with ≤50% (v:v) FWC produced superior seedling emergence, growth, and biomass accumulation. Importantly, no FWC:PM substrate blend produced higher emergence or growth than PM alone. Although leaf properties in FWC:PM mixtures were comparable to or better than those in a commercial PM standard, the observed reduction in uniform and rapid seedling emergence is a more critical factor for commercial production. Thus, FWC may be a suitable material for substrate blends, but it should not serve as a standalone alternative to PM.